Phonological and Orthographic Overlap Effects in Fast and Masked Priming. Issue 9 (September 2014) - Frisson, Steven; Bélanger, Nathalie N.; Rayner, Keith
We investigated how orthographic and phonological information is activated during reading, using a fast priming task, and during single-word recognition, using masked priming. Specifically, different types of overlap between prime and target were contrasted: high orthographic and high phonological overlap ( track–crack ), high orthographic and low phonological overlap ( bear–gear ), or low orthographic and high phonological overlap ( fruit–chute ). In addition, we examined whether (orthographic) beginning overlap ( swoop–swoon ) yielded the same priming pattern as end (rhyme) overlap ( track–crack ). Prime durations were 32 and 50 ms in the fast priming version and 50 ms in the masked priming version, and mode of presentation (prime and target in lower case) was identical. The fast priming experiment showed facilitatory priming effects when both orthography and phonology overlapped, with no apparent differences between beginning and end overlap pairs. Facilitation was also found when prime and target only overlapped orthographically. In contrast, the masked priming experiment showed inhibition for both types of end overlap pairs (with and without phonological overlap) and no difference for begin overlap items. When prime and target only shared principally phonological information, facilitation was only found with a long prime duration in the fast priming experiment, while no differences were found in the masked priming version. These contrasting results suggest that fast priming and masked priming do not necessarily tap into the same type of processing.